(untitled) (The Review of Diabetic Studies, 2025)
Background: Community-acquired respiratory tract infections (CA-RTIs) are among the leading causes of global morbidity and antibiotic use. Despite widespread prescription of amoxicillin-clavulanate, uncertainty persists regarding its comparative efficacy and safety versus other broad-spectrum antibiotics. Objective: To systematically evaluate clinical outcomes, safety profiles, and resistance implications of amoxicillin-clavulanate compared with alternative broad-spectrum agents in adults and children with CA-RTIs. Methods: Following PRISMA 2020 guidelines, 11 peer-reviewed studies published between 2000 and 2025 were analyzed, including randomized controlled trials, observational cohorts, and registry data. Studies comparing amoxicillin-clavulanate with fluoroquinolones, macrolides, cephalosporins, co-trimoxazole, or amoxicillin alone were included. Primary outcomes were clinical cure, mortality, and adverse events. Results: Across studies, amoxicillin-clavulanate demonstrated comparable or superior efficacy to other broad-spectrum antibiotics, with clinical cure rates between 87% and 95% in CAP and AECOPD. Mortality and readmission rates showed no significant difference compared with comparators. Adverse events, primarily gastrointestinal, were slightly higher with amoxicillin-clavulanate. Evidence from large-scale cohorts (Bagge et al., 2021; Wei et al., 2024) and pediatric trials (Gerber et al., 2017; Jehan et al., 2020) supports amoxicillin or amoxicillin-clavulanate as first-line therapies. Conclusions: Amoxicillin-clavulanate remains an effective and generally safe empirical option for CA-RTIs. Narrow-spectrum alternatives such as amoxicillin alone may be equally effective for mild-to-moderate infections, aligning with antibiotic stewardship principles.